2022
DOI: 10.1089/bioe.2021.0044
|View full text |Cite
|
Sign up to set email alerts
|

The Platelet Electrome: Evidence for a Role in Regulation of Function and Surface Interaction

Abstract: Introduction. Platelets protect the body from injury through formation of blood clots, changing from a normal, quiescent state to become "activated" in response to external stimuli such as chemical cues, shear stress and temperature. This causes changes in shape, increased adhesion, and alteration of the electrical properties such as membrane potential Vm and zeta potential ζ. These phenomena have been regarded as largely unconnected; for example, changes in ζ have been attributed solely to alteration of surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 27 publications
4
11
0
Order By: Relevance
“…In previous work with RBCs 12 , and subsequently confirmed with platelets 13 , we demonstrated that modulation of V m alters the ζ-potential. In consequence, developing an understanding of the origin of V m is essential to understand how this relationship occurs.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In previous work with RBCs 12 , and subsequently confirmed with platelets 13 , we demonstrated that modulation of V m alters the ζ-potential. In consequence, developing an understanding of the origin of V m is essential to understand how this relationship occurs.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, recent observations of red blood cells (RBCs) have indicated that the extracellular ζ-potential (a voltage field that arises from a cell surface charge and extends several nanometres from the cell surface) is affected by V m , via a process related to the capacitance of the electrical double-layer 11 . Similar phenomena have also been identified in platelets 12 . Connections have also been identified between V m and passive cellular electrical properties, such as the cytoplasm conductivity σ cyto and the membrane conductance G eff [13][14][15] .…”
supporting
confidence: 83%
See 2 more Smart Citations
“…DEP has revealed circadian cycles in the electrical properties of RBCs ( Henslee et al, 2017 ; Beale et al, 2019 ; Beale et al, 2022 ) human as well as sub-2 h, ultradian rhythms in the RBCs of voles ( Hoettges et al, 2019 ). More recently, connections have been demonstrated between these DEP-derived electrical parameters and other electrical measures of cell function, such as the membrane potential (V m ) and the extracellular electrical potential (the ζ-potential) that regulates the way cells interact with other cells and biological entities in their immediate environment ( Hughes et al, 2021 ; Hughes et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%